Pemberdayaan Ekonomi Masyarakat Petani Jagung Berbasis Kelompok Usaha Tani di Takalar - Irnawati; Irwan Misbach (Jurnal Berita Sosial, 2022)
The main problem in this research is how to empower the economic community of corn farmers based on farmer groups. This study uses a qualitative type of research, using a sociological approach located in Barugaya Village, North Polongbangkeng District, Takalar Regency. The data sources in this study are based on primary data sources and secondary data sources. The data collection techniques carried out are through observation, interviews and documentation. Data analysis was carried out by reducing data, presenting data, then drawing conclusions. The results of this study indicate that the process of economic empowerment of the corn farming community based on farming groups in Barugaya Village is through deliberation that has been successfully carried out by the government supported by the community who are members of farmer groups then counseling and training is carried out by the agricultural office and finally carried out capacity development in empowerment through farmer groups but several obstacles that occur are low public awareness to participate, limited land and budget, uncertain market prices and uncertain weather.